BOXING SPORTS PERSPECTIVES IN SUPPORTING SPORTS PERFORMANCE IN ROKAN HULU REGENCY - Sinurat, Ridwan (Universitas Negeri Medan, 2020)
Boxing is a sport and martial art that features two participants of similar weight competing with each other using their fists in a series of one or three-minute intervals called rounds. The purpose of this study was to determine the perspective of boxing in supporting sports achievements in Rokan Hulu Regency in terms of aspects of organization and management, funding, government support, human resources, infrastructure, fostering and the application of science and technology. Sources of data came from the Boxing Sport Management Board, KONI Management Board, Rokan Hulu Boxing Athletes and Rokan Hulu Boxing Trainer. Data is analyzed by collecting data, reducing data, conveying data and drawing conclusions. The results of the study 1) already have organizational legality with proof of decree Number 05 / SK / PERTINA RIAU / V / 2018. 2) the source of funds remains from KONI Rokan Hulu Regency. Still, the assistance is not sufficient 3) support from the government has not been maximized, 4) human resources are meagre only has one referee and one trainer in the entire Rokan Hulu Regency, 5) infrastructure facilities are very very low far from the official word, only has two pairs of boxing gloves and one sansack, 6) only one boxing club in Tambusai, 7) Application of Science and technology has never been made, even though Rokan Hulu district has two sports campuses namely Pasir Pengaraian University and STKIP Rokania. Suggestions that in the future all lines of society from village, sub-district and district governments to support the existence of boxing in the Rokan Hulu Regency, PERTINA should immediately conduct socialization about boxing in schools in Rokan Hulu and PERTINA districts as well as increase the number of sports human resources such as attending referee training, licensed trainer.